Hepatic stellate cell single cell atlas reveals a highly similar activation process across liver disease aetiologies - Vincent Merens; Elisabeth Knetemann; Elif Gürbüz; Vincent De Smet; Nouredin Messaoudi; Hendrik Reynaert; Stefaan Verhulst; Leo A. van Grunsven (JHEP Reports, 2025)
Background & Aims: The progression of chronic liver disease (CLD) is characterized by excessive extracellular matrix deposition, disrupting hepatic architecture and function. Upon liver injury, hepatic stellate cells (HSCs) differentiate towards myofibroblasts and become inflammatory, proliferative and fibrogenic. To date, it is still unclear whether HSC activation is driven by similar mechanisms in different aetiologies. Methods: HSCs from multiple publicly available single-cell RNA-sequencing datasets were annotated and merged into a single-cell HSC activation atlas. Spheroid co-cultures of primary mouse hepatocytes/HSCs (n = 5) and ELISAs on patient plasma samples (n = 80) were performed to validate the mechanistic insight obtained from the HSC atlas. Results: We established an HSC activation atlas in which HSCs are clearly divided into three distinct transcriptomic profiles: quiescent HSCs, initiatory HSCs and myofibroblasts. These transcriptomic profiles are present in each of the investigated mouse liver injury models as well as in human CLDs, indicating that HSC activation is a conserved process. This activation process is driven by a core set of transcription factors independent of liver injury or species. Furthermore, we reveal novel ligands associated with activation of HSCs in multiple liver injury models and validate the profibrotic effect of parathyroid hormone. Finally, we identify COLEC10 as a conserved marker for quiescent HSCs and a biomarker of liver fibrosis in patients with different CLDs (p <0.0001). Conclusions: We reveal unexpected similarities in the regulatory mechanisms of HSCs across diverse liver injury settings and species. The HSC activation atlas has the potential to provide novel insights into liver fibrosis and steer novel treatment options. Impact and implications:: This study establishes a single-cell atlas of hepatic stellate cells across various liver injuries, highlighting a conserved activation process between different injuries and across species. The discovery of novel activating ligands and the biomarker COLEC10 in human plasma could be used to enhance diagnostic and therapeutic strategies. Additionally, the conserved activation process supports the use of any mouse model for mechanistic studies and testing of new anti-fibrotic compounds, streamlining preclinical research efforts.